PENGARUH CAKUPAN IMUNISASI CAMPAK TERHADAP INCIDENCE RATE PENYAKIT CAMPAK DI INDONESIA TAHUN 2016 - Wijaya, Satriya (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Immunization has proven to be one of the most important public health efforts. The immunization program has shown remarkable success and is a very cost-effective effort in preventing infectious diseases (MOH, 2003). Immunization has also saved so many lives compared to other public health efforts. Very important role of measles immunization in reducing child mortality, so measles immunization become one of indicator in achieving fourth goal of MDGs that is decrease child mortality rate. In this case, what is seen is the proportion of one-year-old children who get measles immunization (WHO, 2014 in the Ministry of Health RI, 2014). The design of this study was cross-sectional with a retrospective approach. The target of this research is all people in Indonesia who are positive for measles. The data used are secondary data derived from the Health Profile of Indonesia Year 2015, to describe the implementation of measles control program in Indonesia in 2016. The variables measured in this study include the success rate of measles immunization coverage in Indonesia in 2016 and the extent of the decrease in measles incidence rate as the impact of measles immunization coverage program in Indonesia in 2016. The overall data used in this study is obtained from data health that is reported on the Health Profile of Indonesia Year 2015. Statistical method used is parametric statistics with the test used is Simple Linear Regression with the help of computer software that is SPSS to help analyze the regression results between the dependent variable and independent variables. The results showed that all infants in Jambi, West Nusa Tenggara, South Sumatera, Central Java and Lampung provinces had measles immunization. Meanwhile, the lowest coverage is Papua with 62.40%, followed by Aceh with 69.60% and West Papua with 73.69%. Then the result of analysis by using simple linear regression statistic test showed that the measles immunization coverage program has an effect on the incidence rate of measles disease with significance value equal to 0,035. In addition, from the research results obtained information that an effective way to prevent measles is the immunization of children under the age of 9 months (<1 year). During the period 2000-2013, measles immunization succeeded in reducing 15.6 million (75%) deaths from measles in Indonesia.